1998
DOI: 10.1002/mds.870130607
|View full text |Cite
|
Sign up to set email alerts
|

Gait analysis in patients with Parkinson's disease and motor fluctuations: Influence of levodopa and comparison with other measures of motor function

Abstract: Although clinical rating scales and simple timed tests of motor function are widely used to assess motor response to therapy, gait analysis may provide an alternative measure of this response. We studied 15 patients with PD complicated by motor fluctuations, first to determine changes in temporal and spatial gait parameters following levodopa, secondly to assess the stability of repeated gait measures and timed tests in "off" and "on" states, and thirdly to determine the use of gait analysis in the assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
51
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 27 publications
9
51
0
4
Order By: Relevance
“…For each subject, the mean of the 3 trials was obtained for the spatiotemporal data. In other studies, 15,16 good repeatability of 3 trials of normal walking has been reported. The selected kinematic and kinetic gait parameters used in the analyses were determined on the routine protocol of the gait analysis laboratory of the Pellenberg University Hospital, Leuven, Belgium.…”
Section: Instrumentation and Proceduresmentioning
confidence: 65%
“…For each subject, the mean of the 3 trials was obtained for the spatiotemporal data. In other studies, 15,16 good repeatability of 3 trials of normal walking has been reported. The selected kinematic and kinetic gait parameters used in the analyses were determined on the routine protocol of the gait analysis laboratory of the Pellenberg University Hospital, Leuven, Belgium.…”
Section: Instrumentation and Proceduresmentioning
confidence: 65%
“…Standardized evaluations using the Unified Parkinson's Disease Rating Scale (UPDRS) 7 and the standwalk-sit test 8 were performed at baseline and 6 months in the offand on-medication states. The UPDRS is a widely used rating scale that evaluates cognitive, functional, and motor deficits (UPDRS part III) and medication-related complications.…”
mentioning
confidence: 99%
“…This conclusion however may be premature, since these types of experiments do not specifically evaluate how individuals with PD are able to incorporate timing cues into an on-going locomotor behaviour. In contrast, temporal characteristics such as cadence have been demonstrated to show no specific response to medications during self-paced locomotion (Blin et al, 1991;Morris et al, 1994a;O'Sullivan et al, 1998). Since step length and gait velocity both increase in response to drug therapy, while timing (which according to physics, is the only other factor that can contribute to gait slowness) is thought to remain constant, it is not surprising that researchers have been quick to assert that the underlying mechanism responsible for gait disturbance in PD involves the scaling and regulation of stride length.…”
Section: Typical Gait Deficits Associated With Parkinson'smentioning
confidence: 99%